A novel multiplex assay for simultaneous quantification of total and S129 phosphorylated human alpha-synuclein - Natalie Landeck (414147) (2016)
Background Alpha-synuclein (asyn) has been shown to play an important role in the neuropathology of Parkinson’s disease (PD). In the diseased brain, classic intraneuronal inclusions called Lewy bodies contain abnormal formations of asyn protein which is mostly phosphorylated at serine 129 (pS129 asyn). This suggests that post-translational modifications may play a role in the pathogenic process. To date, several uniplex assays have been developed in order to quantify asyn not only in the brain but also in cerebrospinal fluid and blood samples in order to correlate asyn levels to disease severity and progression. Notably, only four assays have been established to measure pS129 asyn specifically and none provide simultaneous readout of the total and pS129 species. Therefore, we developed a sensitive high-throughput duplex assay quantifying total and pS129 human asyn (h-asyn) in the same well hence improving accuracy as well as saving time, consumables and samples. Results Using our newly established duplex assay we measured total and pS129 h-asyn in vitro showing that polo-like kinase 2 (PLK2) can phosphorylate asyn up to 41 % in HEK293 cells and in vivo the same kinase phosphorylated h-asyn up to 17 % in rat ventral midbrain neurons. Interestingly, no increase in phosphorylation was observed when PLK2 and h-asyn were co-expressed in rat striatal neurons. Furthermore, using this assay we investigated h-asyn levels in brain tissue samples from patients with PD as well as PD dementia and found significant differences in pS129 h-asyn levels not only between disease tissue and healthy control samples but also between the two distinct disease states especially in hippocampal tissue samples. Conclusions These results demonstrate that our duplex assay for simultaneous quantification is a useful tool to study h-asyn phosphorylation events in biospecimens and will be helpful in studies investigating the precise causative link between post-translational modification of h-asyn and PD pathology. Other Information Published in: Molecular Neurodegeneration License: https://creativecommons.org/licenses/by/4.0/   See article on publisher's website: https://dx.doi.org/10.1186/s13024-016-0125-0